To Refer or Not to Refer: Exploring Family Therapists' Beliefs and Practices Related to the Referral of Lesbian, Gay, and Bisexual Clients. (30th December 2015) - McGeorge, Christi R.; Stone Carlson, Thomas; Farrell, Molly
Abstract : This study explored how negative beliefs toward lesbian, gay, and bisexual (LGB) individuals and LGB clinical competence influenced family therapists' beliefs and practices regarding referring based on the sexual orientation of the client. The sample consisted of 741 experienced clinicians. The results of this study indicated that the majority of the participants believe it is ethical to refer LGB clients; however, most had never made such a referral. Furthermore, participants who had referred based solely on the client's sexual orientation reported higher levels of negative beliefs toward LGB individuals and lower levels of LGB clinical competence. Finally, negative beliefs toward LGB persons not only predicted the practice of referring, but also the belief that it is ethical to refer an LGB client.